ID: 234. Issue 1 (November 2015) - Shin, Danim; Rand, Ulfert; Bergeest, Jan-Philip; Rohr, Karl; Köster, Mario; Hauser, Hansjörg
<x xml:space="preserve">Abstract</x> Early recognition of viral pathogen-associated molecular patterns (PAMPs) by RIG-I-like receptors (RLRs) and endosomal Toll-like receptors (TLRs) is crucial to protect the host from extensive viral propagation. These sensors activate intracellular signaling cascades leading to the induction of type I and type III Interferons (IFNs). During the acute phase of infection the efficiency of the IFN system in time, space and strength determine the outcome of antiviral protection. To understand the dynamics of antiviral activity within a cell community and to define the limiting steps during signal propagation we studied temporal and spatial dynamics of IFN induction and IFN-stimulated gene expression on single-cell level. Time-resolved imaging uncovers a large extent of heterogeneity for several key steps of antiviral activity that is based on stochastic decisions. This heterogeneity applies with respect to the ability of the individual cells to respond as well as with respect to the onset times of the responding population. Especially at lower IFN concentrations the temporal variability of ISG induction increases explicitly. To determine the molecular origin of the heterogeneity upon PAMP recognition we combined single cell reporter systems for K63-polyubiquitination and NF-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qtk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />κ</alternatives>B activation. We find a temporal variability of polyUb aggregation events that is paralleled by subsequent NF-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qtk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />κ</alternatives>B activation. However, the temporal variability between both events was low compared to the overall variability of NF-<alternatives><inline-graphic xlink:href="ark:/27927/pgj2n6x7qtk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />κ</alternatives>B activation onset. We conclude that heterogeneity of the IFN induction results mainly from the dominant stochastic nature of high-order complex formation of RIG-I upon ligand recognition.